2020
DOI: 10.1109/access.2020.3028031
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Vendor Managed Inventory Supply Chain Operations Using Blockchain Smart Contracts

Abstract: Supply chain networks have grown in complexity and size due to increased globalization leading to a variety of challenges and opportunities for improvement. Optimizing inventory levels and adjusting replenishment policies have significant effects on the operational performance and profitability of supply chains. Vendor Managed Inventory (VMI) is a mutually beneficial arrangement between supplier and buyer, where the supplier is responsible for making inventory and replenishment decisions based on buyers' inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 26 publications
(33 reference statements)
0
42
0
1
Order By: Relevance
“…Gas is the unit of calculation for all calculations in Ethereum. In [3] and [29], the authours used Ethereum smart contracts to solve the researched problems, and conducted detailed testing and analysis. The results showed that the use of Ethereum smart contracts can cost-savings and increase stakeholder profits.…”
Section: B Cost Analysis and Problem Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas is the unit of calculation for all calculations in Ethereum. In [3] and [29], the authours used Ethereum smart contracts to solve the researched problems, and conducted detailed testing and analysis. The results showed that the use of Ethereum smart contracts can cost-savings and increase stakeholder profits.…”
Section: B Cost Analysis and Problem Discussionmentioning
confidence: 99%
“…The huge advantage of smart contracts is not only widely used in food safety traceability. Omar et al [29] presented a method based on blockchain, using Ethereum smart contracts and decentralized storage system to automate processes and information exchange, and capture the detailed algorithm of interaction between supply chain stakeholders, provides them with a compact, safe, reliable and transparent communication mode, has solved the Vendor Managed Inventory operation of data integrity, transparency, traceability and single point of failure. Zhang et al [30] proposed a novel secure billing protocol for online ride-hailing vehicles, which solved the difficult problem of fare estimation and automatic payment through smart contracts.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, the Vendor-Managed Inventory (VMI) scheme is one of the most widely used systems for optimizing supply chain performance [11]. It requires supply chain members to collaborate and share inventory information in which the supplier makes the necessary replenishment decisions depending on the current inventory of the retailer and the specific terms and conditions decided upon by both parties.…”
Section: A Benefits Of Inventory Sharingmentioning
confidence: 99%
“…In 2020, Omar et al 24 have proposed a blockchain‐oriented technique with the help of smart contracts for transforming the VMI supply chain operations. A generic framework was developed by means of the decentralized storage systems and Ethereum smart contracts for speeding up the detailed algorithms and information exchange and processes that grabbed the interactions within the supply chain stakeholders.…”
Section: Literature Surveymentioning
confidence: 99%
“…Some of the most important features as well as challenges are shown in Table 1. Blockchain smart contracts 24 offer strong value chain partnership with enhanced trust between the stakeholders and it also promotes strong transparency; improve communication among distinct trading partners, enhanced supply chain performance, and enhanced productivity. But, the smart contract functions are not extended for labeling the multiple requirements of the supply chain industry.…”
Section: Literature Surveymentioning
confidence: 99%